Consequências da privação materna para o comportamento tipo-ansioso: participação do eixo hipotálamo-pituitária-adrenal e do sistema de neurotransmissão GABAaérgico - Faturi, Claudia de Brito [UNIFESP] (2009)
Adverse events in childhood have been associated to the development of psychopathologies, such as depression and anxiety disorders. In rats, stressful events during neonatal period, like 24h Maternal Deprivation (MD), may be an interesting tool to understand how stress during early life leads to changes in behavior and stress response in adulthood. According to some studies, MD on the 3rd day (MD 3-4) or 11th day (MD 11- 12) of life results in opposite changes in the activity of the Hypothalamus-Pituitary- Adrenal (HPA) axis, i.e., hyper and hyporresponsiveness, respectively. Since in human beings psychopathologies has been related to impairment in resilience to stress the aim of this work was to investigate whether MD leads to long lasting changes in HPA axis functioning and differential behavioral features in animal models of anxiety. The results obtained indicate that only the ACTH release presented the pattern we hypothesized. Conversely the corticosterone (CORT) plasmatic levels do not reflect this pattern. Moreover, MD did not affect the CORT release in response to the Dexamethasone Suppression Test, indicating that there are MD did not alter the negative feedback system. Although MD did not lead to convincing alteration to CORT levels it did change anxiety-like behavior in the group MD 11-12. However this behavioral change did not seem to be mediated by expression of benzodiazepine site in GABAA receptors. The results indicate that even though the MD procedure does not lead to consistent changes in the peripheral component of the HPA axis it could still be an interesting animal model to study the neurobiological underpinnings of how adverse events in early life increase the vulnerability to psychopathologies.